In vitro Radioprotective Activity of the Bryozoan Hyalinella punctata - Pejin, Boris; Stanimirovic, Bojana; Djordjevic, Neda; Hegedis, Aleksandar; Karaman, Ivo; Horvatovic, Mladen; Radotic, Ksenija (Asian Journal of Chemistry, 2013)
The objective of the present study was in vitro evaluation of radioprotective activity of the freshwater bryozoan Hyalinella punctata on cultured human peripheral blood lymphocytes after irradiation with 2 Gy of 60Co g-rays. Since its water extract at concentration 0.001 mg/mL reduced the incidence of radiation-induced micronuclei for almost 30 %, it could be considered as a promising source of new natural products with the aforementioned activity. Both the content of sulphur (1.17 %), determined by gravimetric method and infrared absorption frequences (76 % similarity with those of bacitracin) of the investigated extract indicate the presence of organic sulphur compound(s) such as cyclic peptides and polypeptides which might be responsible for the observed radioprotection.